Implementasi Sistem Pendukung Keputusan Metode SWARA untuk Pemilihan Laptop Low-End Terbaik 2024 Bagi Programmer - Rizki Andista Pandapotan Situmorang; Reyhan Abdillah Rangkuti; Iskandar Zulkarnaen Siregar; Divi Handoko (LKP KARYA PRIMA KURSUS, 2025)
The selection of low-end laptops for programmers requires consideration ofvarious criteria, such as technical specifications, price, durability, and performance. Thisstudy develops a Decision Support System (DSS) based on the Step-wise WeightAssessment Ratio Analysis (SWARA) method to assist users in determining the best laptopin 2024. The SWARA method is employed to calculate the weights of criteria in astructured manner, involving expert and user assessments. This process includesidentifying key criteria such as processor, RAM, storage capacity, battery life, and price.The evaluation results show that this method can provide accurate and relevantrecommendations. The SWARA-based DSS is expected to be a practical solution for noviceprogrammers with limited budgets, while also contributing to the advancement ofdecision support systems in the field of information technology.